Development of Academic Resilience Instrument for Junior High School Students : A Rasch Model Analysis - Herdiansyah, Diki; Fauziah, Mufied (LPPM Universitas Pendidikan Mandalika, 2024)
This study aims to develop and test the validity and reliability of an academic resilience instrument tailored to the context of Junior High School (SMP) students. The research was conducted using a quantitative method with a cross-sectional design, involving data collection through a 51-item questionnaire. The subjects of this study were 84 junior high school students aged 12-16 from the Yogyakarta region. Data analysis was carried out using the Rasch Model method with Winstep version 3.73. The analysis results identified 47 items that met the criteria, with a Cronbach’s alpha value of 0.93, which falls into the good category. The person reliability value of 0.92 is considered excellent, while the item reliability value of 0.96 is categorized as outstanding. The analysis results indicate that the developed academic resilience instrument possesses good psychometric characteristics, including high validity and reliability. This instrument can serve as an effective tool for educators and counselors to identify student needs, design appropriate intervention programs, and enhance the quality of guidance and counseling at the junior high school level.